1994
DOI: 10.1093/schbul/20.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Is the Modality-shift Effect Specific for Schizophrenia Patients?

Abstract: Several studies have found that the reaction time of schizophrenia patients is longer when successive imperative stimuli are of different modality (e.g., light followed by sound) than when they are identical (e.g., sound followed by sound). This effect is called the modality-shift effect. In this study, the reaction times of 175 persons were analyzed: 54 schizophrenia patients, 33 patients with mood disorders, 13 alcoholics, 17 patients with rheumatoid arthritis, 13 patients with internal diseases, and 45 norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
(27 reference statements)
5
20
0
Order By: Relevance
“…These results are in line with data from studies addressing the question if the modality shift effect is specific for schizophrenia patients (as originally assumed [16]) and concluding that the increased modality shift effect in reactions to sound stimuli may be a general marker of psychopathology [11]. An increment of the modality shift effect under the condition of long ISI is specific for schizophrenia patients but not for other patients or healthy persons where it is most pronounced in short ISIs [11,17].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results are in line with data from studies addressing the question if the modality shift effect is specific for schizophrenia patients (as originally assumed [16]) and concluding that the increased modality shift effect in reactions to sound stimuli may be a general marker of psychopathology [11]. An increment of the modality shift effect under the condition of long ISI is specific for schizophrenia patients but not for other patients or healthy persons where it is most pronounced in short ISIs [11,17].…”
Section: Discussionsupporting
confidence: 84%
“…light followed by light). The increment of this universal effect is larger in patients with attention deficits, such as schizophrenia patients (where this effect was observed originally), than in healthy subjects [10,11]. The main reason why we decided to apply the modality shift paradigm was that the effect which is expressed as the relation between cross-and ipsimodal reaction times is independent of absolute reaction time or motivation processes [12].…”
Section: Introductionmentioning
confidence: 99%
“…This result presumably reflects the well-known modalityshift effect (see, e.g., Dinnerstein & Zlotogura, 1968;Ferstl, Hanewinkel, & Krag, 1994;Mowrer, Rayman, & Bliss, 1940;Spence & Driver, 1997b; Spence, Driver, & Rogers, 1997). Response latencies were also significantly shorter for auditory targets overall, as in Experiment 2, resulting in a main effect of target modality [F(I,12)~27.7,p~.0002].…”
Section: Resultsmentioning
confidence: 67%
“…Spence and Driver (1997) recently noted that standard analyses for studies with blocked modality-probabilities, which include all trials (as for the analyses presented above and those of Klein, 1977, andPosner et al, 1976), may fail to distinguish the critical effects of expectancy from stimulus-driven effects, such as intertrial repetition effects (see also Epstein & Rock, 1960, on this distinction). Past studies (e.g., Ferstl et al, 1994;Zubin, 1975) have shown that people typically respond more slowly to a target in a given modality if the preceding target occurred in a different modality (thus producing a crossmodal trial), rather than in the same modality (resulting in an ipsimodal trial). This purely stimulus-driven effect has become known as the modality-shifting effect (MSE).…”
Section: Resultsmentioning
confidence: 99%